Patient reported outcomes in a trial of combination therapy with etanercept and methotrexate for rheumatoid arthritis: the TEMPO trial. Issue 3 (3rd August 2005) - van der Heijde, D; Klareskog, L; Singh, A; Tornero, J; Melo-Gomes, J; Codreanu, C; Pedersen, R; Freundlich, B; Fatenejad, S
Abstract : Objective: To compare patient reported measures of function, health related quality of life (QoL), and satisfaction with medication among patients with rheumatoid arthritis (RA) treated with methotrexate (MTX), etanercept, or both for up to 1 year. Methods: In a 52 week, double blind, clinical trial, patients with active RA were randomised to receive etanercept 25 mg twice weekly, methotrexate up to 20 mg weekly, or combination therapy. The Health Assessment Questionnaire (HAQ) disability index, EuroQoL health status visual analogue scale (EQ-5D VAS), patient global assessment, and patient general health VAS were administered at baseline and weeks 2, 4, 8, 12, 16, 20, 24, 32, 40, 48, and 52. Satisfaction with the medication was compared at 52 weeks. Results: Of 682 enrolled patients, 522 completed 52 weeks of treatment. Mean improvement from baseline in HAQ score was 0.65, 0.70, and 1.0 for MTX, etanercept, and the combination, respectively. The mean percentage and absolute improvement in the HAQ was significantly higher (p<0.01) for combination therapy than for either of the monotherapies. Combination therapy produced significantly more rapid achievement of HAQ ⩽0.5 sustained for 6 months than either of the monotherapies (p<0.01). Compared with patients receiving monotherapy, those receiving combination therapy achieved a significantly better (p<0.05) health state as measured by the EQ-5D VAS (mean (SD) 63.7 (3.2), 66.8 (3.2), 72.7 (3.1) for MTX, etanercept, and the combination, respectively). Results were similar for other assessments (p<0.01). Patients in combination and etanercept groups were significantly more likely (p<0.0001, p = 0.0009, respectively) to report satisfaction with the medication. Conclusions: Combination therapy with etanercept and methotrexate improved function, QoL, and satisfaction with the medication significantly more than monotherapy.